Figurative Language in Stephanie Garber's Novel "Once Upon a Broken Heart" - Astini, Ni Luh Putu Nur Sri; Pratiwi, Desak Putu Eka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze figurative language found in the novel "Once Upon a Broken Heart" by Stephanie Garber. The data were analyzed based on Perrine and Arp’s theory of figurative language (1992) and theory of meaning proposed by Leech (1981). This study employs a descriptive qualitative method to analyze the data. The analysis identifies 190 instances of figurative language; 103 instances of simile, 16 instances of metaphor, 23 instances of personification, 31 instances of hyperbole, 11 instances of synecdoche, and 7 instances of irony. The result indicate that simile is the most dominantly used figure of speech because it provides a direct comparison of something uncommon to something common so that the readers could easily understand and quickly visualize the image of what is being compared. The predominance of similes is relevant because it makes the emotional and fantasy aspects of the novel easier to convey, allowing readers to connect with the narrative on a deeper imaginative level.